Interactions of amino acids and hormones regulate the balance between growth and milk protein synthesis in lactating rats fed diets differing in protein content. (30th January 2021) - Xu, Lianbin; Hanigan, Mark D; Lin, Xueyan; Li, Xiuli; Li, Mengmeng; Liu, Wei; Hu, Zhiyong; Hou, Qiuling; Wang, Yun; Wang, Zhonghua
Abstract: Insulin-like growth factor-I (IGF-I ), growth hormone (GH ), and prolactin (PRL ) play important roles in milk protein synthesis, and their plasma concentrations were reported to be affected by dietary protein intake. To investigate the relationship between circulating amino acid (AA ) and concentrations of these hormones, 18 Wistar rats aged 14 wk were assigned to a low (LP ; 9% protein), standard (SP ; 21% protein), or high-protein (HP ; 35% protein) diet from parturition through day 15 of lactation. Plasma, liver, pituitary gland, skeletal muscle, and mammary gland samples were collected at the end of treatment. Circulating and hepatic IGF-I concentrations increased linearly with elevated dietary protein concentrations ( P < 0.0001). Rats receiving the HP diet had higher circulating GH ( P < 0.01) and pituitary PRL concentrations ( P < 0.0001) but lower pituitary GH concentration ( P < 0.0001) relative to those in rats receiving the LP and SP diets. Pearson correlation test performed on composed data across treatments showed that several circulating AAs were correlated with circulating and tissue concentrations of IGF-I, GH, and PRL. Multiple linear regression analyses identified Leu, Gln, Ala, Gly, and Arg as the main AAs associated with hormone responses ( R 2 = 0.37 0.80; P < 0.05). Rats fed the LP and HP diets had greater Igf1 and Ghr gene expression in skeletal muscle than those fed the SP diets ( P < 0.01). However, LP treatment decreased Prlr mRNA abundance in mammary glands as compared with the SP and HP treatments ( P < 0.05). The HP diets increased AA transporter expression ( P < 0.01) but decreased mammalian target of rapamycin ( P < 0.05) and 70 kDa ribosomal protein S6 kinase 1 ( P < 0.01) phosphorylation in mammary glands as compared with the LP and SP diets. The results of the present study suggested that several circulating AAs mediated the effects of dietary protein supply on concentrations of IGF-I, GH, and PRL, which in turn altered the metabolism status in peripheral tissues including the lactating mammary glands.